Bahaya Sering Mengkonsumsi Saus Bantal Kepada Siswa Siswi di SD Negeri 02 Podo - Imam Rosada, Faiq Allam; allam, faiq; alfandi, kurnia; Putri, Mega Widya (STKIP Muhammadiyah Kuningan Secretariat Jurnal Muhammadiyah Untuk Olahraga Indonesia. Building A106 Street of Murtasiah Soepomo No 28b, 45511 Kuningan - West Java Telephone : 0232-874085 Homepage : E-mail:, 2024)
The habit of consuming pillow sauce in children has risks and bad impacts on health. The bad impact of eating sauce because too much sugar enters the body is that it can increase the risk of diabetes and several other dangerous diseases. In our service at SDN 02 Podo, we educate about the dangers of pillow sauce for body health